Reshaping the International Monetary Architecture: Lessons from the Keynes Plan - Piffaretti, Nadia F. (2012)
As we witness profound turmoil in the global economy, and as it becomes apparent that the so-called "Revived Bretton Woods System" might be nothing more than a temporary non sustainable financing of the US structural imbalance favored by the global role of the dollar, which has increased the overall vulnerability of the global financial architecture, it's worth revisiting the origins of the Bretton Woods conference, and pointing out the relevance for today's framework of Keynes' original 1942 plan for an International Clearing Union. In this note we explore the main characteristics of Keynes' original plan, by revisiting his original writings between 1940 and 1944, and we outline its relevance to the current debate on the international financial architecture. We'll argue that reforms of the international financial architecture should include anchoring the international monetary system on sounder institutional ground.